Contaminant transport in wetland flows over bottom-layer absorption subject to wind effect - Mondal, Buddhadeb; Barman, Krishnendu; Saha, Shuvendu; Mazumder, Bijoy S. (Modeling earth systems and environment, 2025)
Ecological decomposition and bottom-layer absorption are omnipresent and greatly influence pollutant mass transport in natural and modeled wetland flows. In addition, it considers the force of wind that blows on the wetland’s surface. The present work analytically explores the two-dimensional and longitudinal mean concentrations under the effects of ecological decomposition, bottom-layer absorption, and wind drag force based on Mei’s homogenization technique up to third-order approximation. The flow velocity is computed from the basic momentum equation under the free-surface wind effect to understand the mechanism behind the pollutant mass transport in wetland flows. Also, from the results it seems that as wind intensity increases, it typically exerts a greater force on the fluid, enhancing the downstream flow velocity. As an extension of the Taylor dispersion model, Mei’s homogenization technique up to third-order approximation is employed for the environmental dispersion processes for the above three factors jointly considered in wetland flows. For large-time scale investing in 2-D concentration distribution, it reveals that 2-D concentration distribution is not uniform in the vertical direction. Moreover, it is concluded that the concentration of pollutants flowing through a wetland is decreased with the increase of bottom-layer absorption parameters. Also, it is seen that when decomposition rate ( ) increases, the pollutant is removed more rapidly, leading to a decrease in the longitudinal mean concentration. For pollutant emission into wetlands, this work is also analytically derived for a critical length and duration of a region influenced by pollutants.